2013
DOI: 10.2340/00015555-1439
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Amyloid Elastosis Revealing Multiple Myeloma with Systemic Amyloidosis

Abstract: Cutaneous amyloid elastosis is a rare presentation of amyloidosis. Only 5 cases have been reported since 1985; 4 in the setting of various presentations of systemic amyloidosis and 1 primary cutaneous localized amyloid elastosis. We report here an additional case, initially misdiagnosed as pseudoxanthoma elasticum (PXE). CASE REPORTA 69-year-old woman was referred for fatigue, dyspnoea on exertion and skin changes. Five years earlier, papules on several aspects of the neck had appeared suddenly (over a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Although amyloid elastosis is very rare, its accurate diagnosis is clinically relevant because it may be the first clue to an undiagnosed systemic amyloidosis, for example, in the context of a clonal B-cell dyscrasia, such as monoclonal gammopathy 2 or multiple myeloma. 3 The diagnosis of amyloid elastosis depends on the dermatopathologist because clinical suspicion of a rare disease with no specific clinical features is unlikely (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although amyloid elastosis is very rare, its accurate diagnosis is clinically relevant because it may be the first clue to an undiagnosed systemic amyloidosis, for example, in the context of a clonal B-cell dyscrasia, such as monoclonal gammopathy 2 or multiple myeloma. 3 The diagnosis of amyloid elastosis depends on the dermatopathologist because clinical suspicion of a rare disease with no specific clinical features is unlikely (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Amyloid elastosis manifests clinically as symmetrically distributed discrete, rubbery, yellow-brown patches, papules, and nodules [1][2][3][4]10 ; itch may be severe. 3 Amyloid elastosisrelated skin changes may be diffused and are frequently located on the body folds, especially the neck, but also in the extremities, trunk, and mucosal sites. 4,10 When the vasculature is prominently affected, there can be sclerodermoid and poikilodermatous changes, cordlike thickening of superficial blood vessels, Raynaud phenomenon, livedo reticularis, and even thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the English-language literature on MEDLINE demonstrated 3 cases that mentioned PXE-like appearance as part of a constellation of cutaneous findings found in amyloid elastosis. 1-3 A total of 5 cases of this entity have been reported [1][2][3][4][5] ; the other 2 cases featured other distinct cutaneous findings but an absence of cutaneous PXE-like plaques. 4,5 Winkelman et al 5 first defined this entity in 1985 based on the finding of striking, disseminated amyloid-coated elastic fibers in visceral, vascular, and subcutaneous sites.…”
Section: Discussionmentioning
confidence: 99%
“…Disseminated accumulation of amyloid around elastic fibers has sometimes accompanied an aggressive course of amyloidosis, as evidenced by 3 reports of lethal outcome. 2,3,5 Further study is required to determine if any prognostic significance is associated with the differentiation of PXElike plaques with normal elastic fibers from amyloid elastosis. Recognition of this unique cutaneous presentation of AL amyloidosis could be instrumental in the early detection and rapid treatment of this severe multisystem disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation